2021
DOI: 10.1038/s41598-021-81720-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress as mediator for longitudinal effects of the COVID-19 lockdown on wellbeing of parents and children

Abstract: Dealing with a COVID-19 lockdown may have negative effects on children, but at the same time might facilitate parent–child bonding. Perceived stress may influence the direction of these effects. Using a longitudinal twin design, we investigated how perceived stress influenced lockdown induced changes in wellbeing of parents and children. A total of 106 parents and 151 children (10–13-year-olds) filled in questionnaires during lockdown and data were combined with data of previous years. We report a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
201
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(226 citation statements)
references
References 43 publications
19
201
3
3
Order By: Relevance
“…These findings extend cross-sectional research conducted in the early phases of the pandemic (Crescentini et al, 2020 ; Cusinato et al, 2020 ; Xie et al, 2020 ) by demonstrating that the severity of child internalizing and externalizing problems are, in fact, higher than before the pandemic. These findings corroborate a handful of prior longitudinal studies (Bignardi et al, 2020 ; Achterberg et al, 2021 ; Cantiani et al, 2021 ) that reported elevated internalizing or externalizing problems during initial lockdowns, compared to pre-pandemic, in the UK, Italy, and the Netherlands. The present findings extend prior work by showing that children continue to experience elevated mental health difficulties while not in lockdown (only 26.5% of the sample was in quarantine at the time of the survey) and several months after the pandemic first began.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings extend cross-sectional research conducted in the early phases of the pandemic (Crescentini et al, 2020 ; Cusinato et al, 2020 ; Xie et al, 2020 ) by demonstrating that the severity of child internalizing and externalizing problems are, in fact, higher than before the pandemic. These findings corroborate a handful of prior longitudinal studies (Bignardi et al, 2020 ; Achterberg et al, 2021 ; Cantiani et al, 2021 ) that reported elevated internalizing or externalizing problems during initial lockdowns, compared to pre-pandemic, in the UK, Italy, and the Netherlands. The present findings extend prior work by showing that children continue to experience elevated mental health difficulties while not in lockdown (only 26.5% of the sample was in quarantine at the time of the survey) and several months after the pandemic first began.…”
Section: Discussionsupporting
confidence: 88%
“…Compared to before the COVID-19 pandemic, during the lockdown in Italy, a sample of preschool children experienced significantly more anxious/depressed behavior, somatic complaints, and aggressive behavior (Cantiani et al, 2021 ). Furthermore, in a sample of 10- to 13-year-olds in the Netherlands, children's perceived stress during the lockdown mediated associations between externalizing behavior prior to the lockdown and elevated externalizing behavior during the lockdown (Achterberg et al, 2021 ). In contrast, a study of predominantly Hispanic/Latinx youth (age 10–14) in the United States (Penner et al, 2020 ) found reductions in internalizing and externalizing problems from before the spread of COVID-19 in the US (January 2020) to during the pandemic (April-May 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Children expressed fear about coronavirus. Due to home confinement and social distancing, children also experienced loneliness, stress, sadness, and depression Achterberg et al 2020 [ 3 ] Netherlands Longitudinal 151 10–13 N.A Children’s externalising behaviour changes were mediated by perceived stress ( p < 0.001): higher scores before lockdown were related to higher stress during the lockdown, Perceived stress in children was associated with negative coping strategies ( p = 0.006). Children’s stress levels were influenced by prior and current parental over-reactivity ( p = 0.001) Adibelli et al 2020 [ 4 ] Turkey Cross-sectional 597 56% 9.9 ± 2.0, 7–13 ★★ The emotional well-being ( p < 0.001), self-esteem ( p < 0.001), family ( p < 0.01), school ( p < 0.05) sub-dimensions and total ( p < 0.05) scores of children who tended to use the internet were found to be lower.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has focused on the unprecedented challenges the COVID-19 pandemic has created for families-including illness, unemployment, and increased caretaking responsibilities-and the associated increase in mental health problems that have occurred for both children and adults. [1][2][3][4][5][6][7][8][9] However, little research has focused on the impact of the pandemic on the social lives of children and adolescents. Difficulties in peer relationships are strongly associated with youth psychopathology.…”
mentioning
confidence: 99%